Examining the Association Between Referral Quality, Wait Time and Patient Outcomes for Patients Referred to an IBD Specialty Program. Issue 4 (20th February 2019) - Mathias, Holly; Heisler, Courtney; Morrison,, Julia; Currie, Barbara; Phalen-Kelly, Kelly; Jones, Jennifer
Abstract: Background: Most speciality inflammatory bowel disease (IBD) care can only be accessed through a referral. Timely access to specialty care has been associated with improved disease-related outcomes. To receive appropriate care, the referral needs to include high-quality information. To date, no research has explored the association between referral quality and IBD patient outcomes. The study objectives were to determine if the quality of referrals to a collaborative IBD program influenced triage accuracy, wait times and patient outcomes. Methods: Two hundred referrals to a collaborative IBD program in Canada for patients with confirmed or suspected IBD were reviewed. Referral quality was evaluated using an evidence- and consensus-based metric. The association between referral quality and patient outcomes (wait time, hospitalizations, disease flares and additional referrals) for semi-urgent referrals was assessed through multivariate analysis. Results: The majority of referrals for IBD speciality care were categorized as being low quality. Referral quality was not significantly associated with any of the patient outcomes; however, longer wait times significantly increased the occurrence of disease flares, hospitalizations and additional referrals while waiting for an IBD specialist appointment. Conclusion: Prolonged wait times for IBD patients are significantly associated with poor patient outcomes and increased costs for the health care system. Although there is literature that suggests that referral quality may be associated with wait time, it is still unclear how it relates to wait time and patient outcomes. Moving forward, the current referral process needs to be critically addressed in order to improve wait times and patient outcomes.